Transforming Leadership Styles in Facing the Challenges of the Digital Era: A Systematic Literature Review - D A Gladysia Sistadanta Kurnia Dewi Sutedja; Made Irma Dwiputranti; I Gusti Ayu Prabandari Tri Putri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The development of digital technology has brought significant changes to the way organizations operate, communicate, and manage human resources. This change requires a transformation in leadership styles that is not only oriented towards managerial skills, but also on technological mastery, flexibility, innovation, and the ability to build collaboration. This study aims to examine the transformation of leadership styles in facing the challenges of the digital era and identify relevant leadership models to support organizational success. The method used is a Systematic Literature Review (SLR) with the PRISMA approach through the stages of identification, selection, feasibility, and inclusion. Literature was obtained from Google Scholar using keywords related to leadership style transformation and leadership in the digital era. The results of the study indicate that leadership transformation occurs in various sectors, such as government, education, business organizations, and information services. The leadership styles that are often recommended are digital, transformational, adaptive, democratic, and participatory leadership. These styles play a role in improving communication, collaboration, innovation, employee engagement, learning quality, and the organization's ability to adapt to technological changes. Thus, leadership in the digital era requires a clear vision, empathy, openness to change, continuous learning capabilities, and the strategic use of technology to create an innovative, productive, and responsive organization.